PENGARUH RETURN ON ASSETS, LEVERAGE, DAN PENGUNGKAPAN TATA KELOLA PERUSAHAAN TERHADAP TAX AVOIDANCE - Febriani, Erika; Trisnawati, Estralita (Jurnal Paradigma Akuntansi, 2024)
This study was implemented in order to measure the relationship between asset returns, leverage, and corporate governance on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Sourced from secondary data through the official website of the Indonesia Stock Exchange, this study involved 93 samples with a period of three years. Data processing was carried out using E-view 10 software. This study concluded that the return on assets was stated to have a significant positive effect on tax avoidance, leverage was stated to have a significant positive effect on tax avoidance, and controlled by a company that was stated to significantly influence tax avoidance.